The use of computer adaptive tests in outcome assessments following upper limb trauma: a systematic review. (June 2018) - Jayakumar, P.; Overbeek, C. L.; Vranceanu, A-M.; Williams, M.; Lamb, S.; Ring, D.; Gwilym, S.
Abstract : Aims: Outcome measures quantifying aspects of health in a precise, efficient, and user-friendly manner are in demand. Computer adaptive tests (CATs) may overcome the limitations of established fixed scales and be more adept at measuring outcomes in trauma. The primary objective of this review was to gain a comprehensive understanding of the psychometric properties of CATs compared with fixed-length scales in the assessment of outcome in patients who have suffered trauma of the upper limb. Study designs, outcome measures and methodological quality are defined, along with trends in investigation. Materials and Methods: A search of multiple electronic databases was undertaken on 1 January 2017 with terms related to "CATs", "orthopaedics", "trauma", and "anatomical regions". Studies involving adults suffering trauma to the upper limb, and undergoing any intervention, were eligible. Those involving the measurement of outcome with any CATs were included. Identification, screening, and eligibility were undertaken, followed by the extraction of data and quality assessment using the Consensus-Based Standards for the Selection of Health Measurement Instruments (COSMIN) criteria. The review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria and reg istered (PROSPERO: CRD42016053886). Results: A total of 31 studies reported trauma conditions alone, or in combination with non-traumatic conditions using CATs. Most were cross-sectional with varying level of evidence, number of patients, type of study, range of conditions and methodological quality. CATs correlated well with fixed scales and had minimal or no floor-ceiling effects. They required significantly fewer questions and/or less time for completion. Patient-Reported Outcomes Measurement Information System (PROMIS) CATs were the most frequently used, and the use of CATs is increasing. Conclusion: Early studies show valid and reliable outcome measurement with CATs performing as well as, if not better than, established fixed scales. Superior properties such as floor-ceiling effects and ease of use support their use in the assessment of outcome after trauma. As CATs are being increasingly used in patient outcomes research, further psychometric evaluation, especially involving longitudinal studies and groups of patients with specific injuries are required to inform clinical practice using these contemporary measures. Cite this article: Bone Joint J 2018;100-B:693–702.